GROWING FROM SEEDS IN THE FIELD CHELEDONIUM MAJUS L. (American Journal of Pedagogical and Educational Research, 2022)
Today, the world has significantly increased interest in natural medicines. For example, in Germany, 80% of doctors of all specialties regularly use plants in their practice. Use 80% of patients in all countries of the world most of them were at least once processed with herbal medicine. Therefore, inventorying common medicinal plants, accounting for their stocks and finding ways to rationally use them is a very urgent task. To this end, in the field, they studied the germination of the seeds of cheledonia of the May, introduced in the Samarkand region [ 3.4 ].